2013
DOI: 10.3109/09638288.2013.822023
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in patients with amputation because of Complex Regional Pain Syndrome type I

Abstract: The results confirmed our hypothesis that patients with an amputation because of CRPS-I who have a higher resilience also have a higher quality of life and experience lower psychological distress. The prognostic value of resilience in this patient group requires further research. Implications for Rehabilitation Until characteristics of patients with positive quality of life outcome have been further unraveled, amputation for CRPS-I should only be performed in expertise centers. Resilience, the process of adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
(49 reference statements)
0
12
1
Order By: Relevance
“…He suggested, after gathering results, that if allodynia is present at the level of amputation it can lead to recurrence. On the other hand, results from Bodde et al 19 and Midbari et al 23 did not support this idea. Mitton et al 29 and Kashy et al 30 each reported one case with amputation of a leg followed by significant improvement in quality of life and rehabilitation.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…He suggested, after gathering results, that if allodynia is present at the level of amputation it can lead to recurrence. On the other hand, results from Bodde et al 19 and Midbari et al 23 did not support this idea. Mitton et al 29 and Kashy et al 30 each reported one case with amputation of a leg followed by significant improvement in quality of life and rehabilitation.…”
Section: Resultsmentioning
confidence: 86%
“…De Boer et al 25 mentioned trans-femoral level of amputation in three patients but did not explain whether it was through healthy skin margins or CRPS site. Bodde et al 19 reported 20 amputations of lower limbs and six of upper limbs, with 81% of amputations through healthy skin and the rest either at or below the level of allodynia. They proposed that level of amputation did not affect the recurrence in contrast to previous reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous cross sectional study in patients with an amputation because of longstanding therapy resistant CRPS-I we found that higher resilience scores were associated with a better QOL and lower psychological distress. [43] In that study we found that the resilience of our participants was above average. We wondered why.…”
Section: Discussionmentioning
confidence: 69%